Cold-application flame-retardant filling paste for optical cable and preparation method of cold-application flame-retardant filling paste

By preparing a cold-application flame-retardant filler paste for optical cables, which is composed of composite modified polymers and flame retardants, the problem of optical cables being easily damaged in harsh environments has been solved. This process achieves excellent flame retardant and mechanical properties, extending the service life of optical cables.

CN119314737APending Publication Date: 2025-01-14SHANGHAI HONGHUI OPTICS COMM TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411531237.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-30
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

Existing optical cables are easily damaged in harsh climates and flammable environments, affecting information transmission performance, and ordinary cable paste has limited effectiveness in cold applications.

Method used

A cold-application flame-retardant filler paste for optical cables is prepared using composite modified polymers, flame retardants, and thickeners. Through a step-by-step mixing and vacuum degassing process, a filler paste with excellent compatibility and flame-retardant properties is formed.

Benefits of technology

It improves the flame retardant and mechanical properties of optical cables, prevents water penetration, extends service life, reduces high-temperature stress corrosion, and enhances protection in high-temperature environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119314737A_ABST
    Figure CN119314737A_ABST
Patent Text Reader

Abstract

The invention discloses cold-applied flame-retardant filling paste for an optical cable and a preparation method of the cold-applied flame-retardant filling paste. The cold-applied flame-retardant filling paste is prepared from the following components: base oil, a composite modified high-molecular polymer, a thickening agent, a flame retardant, ethylene triethoxysilane and sodium polyacrylate. The prepared cold-applied flame-retardant filling paste for the optical cable has excellent compatibility, high and low temperature resistance and excellent flame retardance, when the cold-applied flame-retardant filling paste is applied to the optical cable, a cable core of the optical cable can be sufficiently protected, stress corrosion of the optical cable in a high-temperature environment can be reduced, and the service life of the optical cable can be prolonged. The filling material can be suitable for filling gaps among various different types of optical cable elements, so that water or other fluids can be effectively prevented from flowing into the gaps of the optical cable elements, and the protection effect of the filling material is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of filling pastes, in particular to a cold-applied flame-retardant filling paste for optical cables and a preparation method thereof. Background Art

[0002] With the rapid development of optical communication, the demand for optical cables is increasing day by day. The booming optical communication industry has brought great convenience to people's daily lives. People's daily lives (mobile phones, computers, televisions, the Internet, etc.) are inseparable from optical communications, which rely on optical cables to transmit information.

[0003] As a new type of cable that integrates power transmission and optical information transmission, optical cable has shown great potential and broad application prospects in fields such as smart grid, communication network and new energy.

[0004] Optical cables are used in non-traditional but efficient ways in certain scenarios or needs. These applications may involve remote areas, complex terrain, special climates and other conditions, which place higher demands on the performance of the cables.

[0005] The performance of optical cables is directly related to their service life and has a very important impact on the smooth operation of optical communications.

[0006] Once the optical cable is subjected to stress, corrosion and hydrogen loss, the information transmission performance of the optical cable will be greatly reduced. Especially when the optical cable is under severe high temperature climate conditions or in a burning environment, the optical cable will completely lose its information transmission performance, causing great inconvenience in daily life and work.

[0007] In optical cable products, ordinary cable paste is mainly used to prevent water seepage and moisture in the optical cable. However, over time, especially in harsh climate environments, it is easy to be damaged, which will directly affect the transmission performance of the optical cable. In addition, it is subject to more restrictions in cold applications.

[0008] Therefore, the present invention solves the corresponding problems by providing a cold-applied flame-retardant filling paste for optical cables. Summary of the invention

[0009] The object of the present invention is to provide a cold-applied flame-retardant filling paste for optical cables to solve the deficiencies in the prior art.

[0010] The technical solution adopted by the present invention is as follows:

[0011] A cold-applied flame-retardant filling paste for optical cables comprises the following ingredients by weight: 55-80 parts of base oil, 23-25 ​​parts of composite modified high molecular polymer, 10-12 parts of thickener, 1-3 parts of flame retardant, 2-4 parts of ethylene triethoxysilane and 1-1.8 parts of sodium polyacrylate.

[0012] As a further technical solution: the method for preparing the composite modified high molecular polymer comprises:

[0013] First, the rubber mixture is added to the solvent and stirred to obtain a rubber solution;

[0014] Adjust the temperature of the rubber solution to 45°C, keep it warm for 20 minutes, and set aside;

[0015] Formic acid and hydrogen peroxide were added to the rubber solution in sequence, and stirred at 500 r / min for 2 hours under the protection of an inert atmosphere, and then the modified bentonite was added, and the stirring reaction was continued for 4 hours, and then cooled to room temperature to obtain a reaction mixture;

[0016] The reaction mixture was flocculated in an ethanol solution for 5 times and filtered to obtain a gel sample;

[0017] The gel sample is dried to obtain a composite modified high molecular polymer.

[0018] As a further technical solution: the rubber mixture is a mixture of styrene-butadiene rubber and EPDM rubber;

[0019] Among them, the mixing mass ratio of styrene butadiene rubber and EPDM rubber is 1:3.

[0020] As a further technical solution: the solvent is an organic solvent;

[0021] The organic solvent is chlorobenzene;

[0022] The mass fraction of the rubber solution is 10-12%.

[0023] As a further technical solution: the mixing mass ratio of the formic acid, hydrogen peroxide and rubber solution is 2:1:100;

[0024] The inert atmosphere is a nitrogen atmosphere;

[0025] The mixing mass ratio of rubber solution and modified bentonite is 100:2-2.5.

[0026] As a further technical solution: the modified bentonite preparation method is:

[0027] First, vinyl acetate is added to methanol, and the mixture is stirred and mixed to obtain a vinyl acetate solution;

[0028] Bentonite and stearic acid were added to the vinyl acetate solution in sequence, and then the initiator was added, the temperature was adjusted to 80°C, the mixture was kept warm and stirred for 4 hours, and then cooled to room temperature, filtered, washed, and dried at 60°C for 1 hour to obtain modified bentonite.

[0029] As a further technical solution: the mass ratio of vinyl acetate to methanol is 1:5;

[0030] The mixed mass ratio of the bentonite, stearic acid and vinyl acetate solution is 3-4:1-1.2:10-14.

[0031] As a further technical solution: the initiator is dibenzoyl peroxide;

[0032] The mass ratio of dibenzoyl peroxide to vinyl acetate is 1:5-6.

[0033] As a further technical solution: the base oil is fluoroether oil;

[0034] The thickener is octamethylcyclotetrasiloxane polymer;

[0035] The flame retardant is magnesium hydroxide.

[0036] A method for preparing a cold-applied flame-retardant filling paste for an optical cable comprises the following steps:

[0037] S1 Preparation:

[0038] Weigh the following according to weight: base oil, composite modified high molecular polymer, thickener, flame retardant, ethylene triethoxysilane, sodium polyacrylate;

[0039] S2 Warm-up:

[0040] Preheat the base oil to 180°C and keep warm for 20 minutes;

[0041] S3 step-by-step insulation mixing:

[0042] Add the composite modified high molecular polymer, ethylene triethoxysilane and sodium polyacrylate to the preheated base oil in sequence, and stir for 2 hours under heat preservation;

[0043] S4 step-by-step cooling and mixing:

[0044] The base oil temperature was lowered to 150°C, a thickener was added to the base oil, and the mixture was stirred and mixed for 40 minutes. The temperature was then lowered to 100°C, a flame retardant was added to the base oil, and the mixture was stirred for 2 hours. The mixture was vacuum degassed to obtain a finished product.

[0045] Beneficial effects:

[0046] The cold-applied flame-retardant filling paste for optical cables prepared by the present invention has excellent compatibility, high and low temperature resistance and excellent flame retardant performance. When applied to optical cables, the cable core of the optical cables can be adequately protected, stress corrosion of the optical cables in high temperature environments can be reduced, and the service life of the optical cables can be increased. The cold-applied flame-retardant filling paste for optical cables prepared by the present invention can be applied to fill the gaps between various types of optical cable components, thereby effectively preventing water or other fluids from flowing into the gaps between optical cable components, thereby increasing the protective effect thereof.

[0047] Magnesium hydroxide and a composite modified high molecular polymer are introduced into the cold-applied flame-retardant filling paste for optical cables prepared by the present invention. Through the combination of the two, a decomposition reaction occurs at high temperature and a large amount of heat is absorbed. This endothermic effect can significantly reduce the temperature, thereby slowing down or preventing the combustion reaction, showing an excellent flame-retardant effect.

[0048] After testing, the oxygen index of the cold-applied flame-retardant filling paste for cables prepared by the present invention is greater than 32%, and the flame-retardant effect is excellent.

[0049] When the optical cable is subjected to external stress impact, the filling paste inside it will flow in the direction of the stress. As the filling paste flows, the viscosity will drop rapidly, thereby greatly reducing the impact of stress on the inner core of the optical cable, thereby improving the protection of the optical cable.

[0050] The present invention can greatly improve the flame retardancy, mechanical properties and anti-permeability properties of the optical cable through the synergistic effect produced by multiple components, greatly improve the quality of the optical cable product, and extend the service life of the optical cable product. BRIEF DESCRIPTION OF THE DRAWINGS

[0051] Figure 1 The present invention is a flow chart of a method for preparing a cold-applied flame-retardant filling paste for optical cables. DETAILED DESCRIPTION

[0052] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0053] The following are specific embodiments

[0054] Example 1

[0055] A method for preparing a cold-applied flame-retardant filling paste for an optical cable comprises the following steps:

[0056] S1 Preparation:

[0057] Weigh the following components in parts by weight: 55 parts of fluoroether oil, 23 parts of composite modified high molecular polymer, 10 parts of octamethylcyclotetrasiloxane polymer, 1 part of magnesium hydroxide, 2 parts of ethylenetriethoxysilane, and 1 part of sodium polyacrylate.

[0058] The method for preparing the composite modified high molecular polymer comprises:

[0059] First, the rubber mixture is added to the solvent and stirred to obtain a rubber solution;

[0060] Adjust the temperature of the rubber solution to 45°C, keep it warm for 20 minutes, and set aside;

[0061] Formic acid and hydrogen peroxide were added to the rubber solution in sequence, and stirred at 500 r / min for 2 hours under the protection of an inert atmosphere, and then the modified bentonite was added, and the stirring reaction was continued for 4 hours, and then cooled to room temperature to obtain a reaction mixture;

[0062] The reaction mixture was flocculated in an ethanol solution for 5 times and filtered to obtain a gel sample;

[0063] The gel sample is dried to obtain a composite modified high molecular polymer.

[0064] The rubber mixture is a mixture of styrene-butadiene rubber and EPDM rubber;

[0065] Among them, the mixing mass ratio of styrene butadiene rubber and EPDM rubber is 1:3.

[0066] The solvent is an organic solvent;

[0067] The organic solvent is chlorobenzene;

[0068] The mass fraction of the rubber solution is 10%.

[0069] The mixing mass ratio of formic acid, hydrogen peroxide and rubber solution is 2:1:100;

[0070] The inert atmosphere is a nitrogen atmosphere;

[0071] The mixing mass ratio of rubber solution and modified bentonite is 100:2.

[0072] The preparation method of modified bentonite is:

[0073] First, vinyl acetate is added to methanol, and the mixture is stirred and mixed to obtain a vinyl acetate solution;

[0074] Bentonite and stearic acid were added to the vinyl acetate solution in sequence, and then the initiator was added, the temperature was adjusted to 80°C, the mixture was kept warm and stirred for 4 hours, and then cooled to room temperature, filtered, washed, and dried at 60°C for 1 hour to obtain modified bentonite.

[0075] The mass ratio of vinyl acetate to methanol is 1:5;

[0076] The mixed mass ratio of the bentonite, stearic acid and vinyl acetate solution is 3:1:10.

[0077] The initiator is dibenzoyl peroxide;

[0078] The mass ratio of dibenzoyl peroxide to vinyl acetate is 1:5.

[0079] S2 Warm-up:

[0080] Preheat the base oil to 180°C and keep warm for 20 minutes;

[0081] S3 step-by-step insulation mixing:

[0082] Add the composite modified high molecular polymer, ethylene triethoxysilane and sodium polyacrylate to the preheated base oil in sequence, and stir for 2 hours under heat preservation;

[0083] S4 step-by-step cooling and mixing:

[0084] The base oil temperature was lowered to 150°C, a thickener was added to the base oil, and the mixture was stirred and mixed for 40 minutes. The temperature was then lowered to 100°C, a flame retardant was added to the base oil, and the mixture was stirred for 2 hours. The mixture was vacuum degassed to obtain a finished product.

[0085] Example 2

[0086] A method for preparing a cold-applied flame-retardant filling paste for an optical cable comprises the following steps:

[0087] S1 Preparation:

[0088] Weigh the following components in parts by weight: 60 parts of fluoroether oil, 24 parts of composite modified high molecular polymer, 11 parts of octamethylcyclotetrasiloxane polymer, 2 parts of magnesium hydroxide, 2.5 parts of ethylenetriethoxysilane, and 1.2 parts of sodium polyacrylate.

[0089] The method for preparing the composite modified high molecular polymer comprises:

[0090] First, the rubber mixture is added to the solvent and stirred to obtain a rubber solution;

[0091] Adjust the temperature of the rubber solution to 45°C, keep it warm for 20 minutes, and set aside;

[0092] Formic acid and hydrogen peroxide were added to the rubber solution in sequence, and stirred at 500 r / min for 2 hours under the protection of an inert atmosphere, and then the modified bentonite was added, and the stirring reaction was continued for 4 hours, and then cooled to room temperature to obtain a reaction mixture;

[0093] The reaction mixture was flocculated in an ethanol solution for 5 times and filtered to obtain a gel sample;

[0094] The gel sample is dried to obtain a composite modified high molecular polymer.

[0095] The rubber mixture is a mixture of styrene-butadiene rubber and EPDM rubber;

[0096] Among them, the mixing mass ratio of styrene butadiene rubber and EPDM rubber is 1:3.

[0097] The solvent is an organic solvent;

[0098] The organic solvent is chlorobenzene;

[0099] The mass fraction of the rubber solution is 11%.

[0100] The mixing mass ratio of formic acid, hydrogen peroxide and rubber solution is 2:1:100;

[0101] The inert atmosphere is a nitrogen atmosphere;

[0102] The mixing mass ratio of rubber solution and modified bentonite is 100:2.1.

[0103] The preparation method of modified bentonite is:

[0104] First, vinyl acetate is added to methanol, and the mixture is stirred and mixed to obtain a vinyl acetate solution;

[0105] Bentonite and stearic acid were added to the vinyl acetate solution in sequence, and then the initiator was added, the temperature was adjusted to 80°C, the mixture was kept warm and stirred for 4 hours, and then cooled to room temperature, filtered, washed, and dried at 60°C for 1 hour to obtain modified bentonite.

[0106] The mass ratio of vinyl acetate to methanol is 1:5;

[0107] The mixed mass ratio of the bentonite, stearic acid and vinyl acetate solution is 3.5:1.1:12.

[0108] The initiator is dibenzoyl peroxide;

[0109] The mass ratio of dibenzoyl peroxide to vinyl acetate is 1:5.5.

[0110] S2 Warm-up:

[0111] Preheat the base oil to 180°C and keep warm for 20 minutes;

[0112] S3 step-by-step insulation mixing:

[0113] Add the composite modified high molecular polymer, ethylene triethoxysilane and sodium polyacrylate to the preheated base oil in sequence, and stir for 2 hours under heat preservation;

[0114] S4 step-by-step cooling and mixing:

[0115] The base oil temperature was lowered to 150°C, a thickener was added to the base oil, and the mixture was stirred and mixed for 40 minutes. The temperature was then lowered to 100°C, a flame retardant was added to the base oil, and the mixture was stirred for 2 hours. The mixture was vacuum degassed to obtain a finished product.

[0116] Example 3

[0117] A method for preparing a cold-applied flame-retardant filling paste for an optical cable comprises the following steps:

[0118] S1 Preparation:

[0119] Weigh the following components in parts by weight: 60 parts of fluoroether oil, 24 parts of composite modified high molecular polymer, 11 parts of octamethylcyclotetrasiloxane polymer, 2 parts of magnesium hydroxide, 2.5 parts of ethylenetriethoxysilane, and 1.5 parts of sodium polyacrylate.

[0120] The method for preparing the composite modified high molecular polymer comprises:

[0121] First, the rubber mixture is added to the solvent and stirred to obtain a rubber solution;

[0122] Adjust the temperature of the rubber solution to 45°C, keep it warm for 20 minutes, and set aside;

[0123] Formic acid and hydrogen peroxide were added to the rubber solution in sequence, and stirred at 500 r / min for 2 hours under the protection of an inert atmosphere, and then the modified bentonite was added, and the stirring reaction was continued for 4 hours, and then cooled to room temperature to obtain a reaction mixture;

[0124] The reaction mixture was flocculated in an ethanol solution for 5 times and filtered to obtain a gel sample;

[0125] The gel sample is dried to obtain a composite modified high molecular polymer.

[0126] The rubber mixture is a mixture of styrene-butadiene rubber and EPDM rubber;

[0127] Among them, the mixing mass ratio of styrene butadiene rubber and EPDM rubber is 1:3.

[0128] The solvent is an organic solvent;

[0129] The organic solvent is chlorobenzene;

[0130] The mass fraction of the rubber solution is 11.5%.

[0131] The mixing mass ratio of formic acid, hydrogen peroxide and rubber solution is 2:1:100;

[0132] The inert atmosphere is a nitrogen atmosphere;

[0133] The mixing mass ratio of rubber solution and modified bentonite is 100:2.3.

[0134] The preparation method of modified bentonite is:

[0135] First, vinyl acetate is added to methanol, and the mixture is stirred and mixed to obtain a vinyl acetate solution;

[0136] Bentonite and stearic acid were added to the vinyl acetate solution in sequence, and then the initiator was added, the temperature was adjusted to 80°C, the mixture was kept warm and stirred for 4 hours, and then cooled to room temperature, filtered, washed, and dried at 60°C for 1 hour to obtain modified bentonite.

[0137] The mass ratio of vinyl acetate to methanol is 1:5;

[0138] The mixed mass ratio of the bentonite, stearic acid and vinyl acetate solution is 3.8:1.1:13.

[0139] The initiator is dibenzoyl peroxide;

[0140] The mass ratio of dibenzoyl peroxide to vinyl acetate is 1:5.2.

[0141] S2 Warm-up:

[0142] Preheat the base oil to 180°C and keep warm for 20 minutes;

[0143] S3 step-by-step insulation mixing:

[0144] Add the composite modified high molecular polymer, ethylene triethoxysilane and sodium polyacrylate to the preheated base oil in sequence, and stir for 2 hours under heat preservation;

[0145] S4 step-by-step cooling and mixing:

[0146] The base oil temperature was lowered to 150°C, a thickener was added to the base oil, and the mixture was stirred and mixed for 40 minutes. The temperature was then lowered to 100°C, a flame retardant was added to the base oil, and the mixture was stirred for 2 hours. The mixture was vacuum degassed to obtain a finished product.

[0147] Example 4

[0148] A method for preparing a cold-applied flame-retardant filling paste for an optical cable comprises the following steps:

[0149] S1 Preparation:

[0150] Weigh out the following components in parts by weight: 65 parts of fluoroether oil, 24 parts of composite modified high molecular polymer, 11 parts of octamethylcyclotetrasiloxane polymer, 2.5 parts of magnesium hydroxide, 3 parts of ethylenetriethoxysilane, and 1.6 parts of sodium polyacrylate.

[0151] The method for preparing the composite modified high molecular polymer comprises:

[0152] First, the rubber mixture is added to the solvent and stirred to obtain a rubber solution;

[0153] Adjust the temperature of the rubber solution to 45°C, keep it warm for 20 minutes, and set aside;

[0154] Formic acid and hydrogen peroxide were added to the rubber solution in sequence, and stirred at 500 r / min for 2 hours under the protection of an inert atmosphere, and then the modified bentonite was added, and the stirring reaction was continued for 4 hours, and then cooled to room temperature to obtain a reaction mixture;

[0155] The reaction mixture was flocculated in an ethanol solution for 5 times and filtered to obtain a gel sample;

[0156] The gel sample is dried to obtain a composite modified high molecular polymer.

[0157] The rubber mixture is a mixture of styrene-butadiene rubber and EPDM rubber;

[0158] Among them, the mixing mass ratio of styrene butadiene rubber and EPDM rubber is 1:3.

[0159] The solvent is an organic solvent;

[0160] The organic solvent is chlorobenzene;

[0161] The mass fraction of the rubber solution is 10.5%.

[0162] The mixing mass ratio of formic acid, hydrogen peroxide and rubber solution is 2:1:100;

[0163] The inert atmosphere is a nitrogen atmosphere;

[0164] The mixing mass ratio of rubber solution and modified bentonite is 100:2.3.

[0165] The preparation method of modified bentonite is:

[0166] First, vinyl acetate is added to methanol, and the mixture is stirred and mixed to obtain a vinyl acetate solution;

[0167] Bentonite and stearic acid were added to the vinyl acetate solution in sequence, and then the initiator was added, the temperature was adjusted to 80°C, the mixture was kept warm and stirred for 4 hours, and then cooled to room temperature, filtered, washed, and dried at 60°C for 1 hour to obtain modified bentonite.

[0168] The mass ratio of vinyl acetate to methanol is 1:5;

[0169] The mixed mass ratio of the bentonite, stearic acid and vinyl acetate solution is 3.5:1.1:12.

[0170] The initiator is dibenzoyl peroxide;

[0171] The mass ratio of dibenzoyl peroxide to vinyl acetate is 1:5.8.

[0172] S2 Warm-up:

[0173] Preheat the base oil to 180°C and keep warm for 20 minutes;

[0174] S3 step-by-step insulation mixing:

[0175] Add the composite modified high molecular polymer, ethylene triethoxysilane and sodium polyacrylate to the preheated base oil in sequence, and stir for 2 hours under heat preservation;

[0176] S4 step-by-step cooling and mixing:

[0177] The base oil temperature was lowered to 150°C, a thickener was added to the base oil, and the mixture was stirred and mixed for 40 minutes. The temperature was then lowered to 100°C, a flame retardant was added to the base oil, and the mixture was stirred for 2 hours. The mixture was vacuum degassed to obtain a finished product.

[0178] Example 5

[0179] A method for preparing a cold-applied flame-retardant filling paste for an optical cable comprises the following steps:

[0180] S1 Preparation:

[0181] Weigh the following components in parts by weight: 70 parts of fluoroether oil, 25 parts of composite modified high molecular polymer, 12 parts of octamethylcyclotetrasiloxane polymer, 3 parts of magnesium hydroxide, 4 parts of ethylenetriethoxysilane, and 1.8 parts of sodium polyacrylate.

[0182] The method for preparing the composite modified high molecular polymer comprises:

[0183] First, the rubber mixture is added to the solvent and stirred to obtain a rubber solution;

[0184] Adjust the temperature of the rubber solution to 45°C, keep it warm for 20 minutes, and set aside;

[0185] Formic acid and hydrogen peroxide were added to the rubber solution in sequence, and stirred at 500 r / min for 2 hours under the protection of an inert atmosphere, and then the modified bentonite was added, and the stirring reaction was continued for 4 hours, and then cooled to room temperature to obtain a reaction mixture;

[0186] The reaction mixture was flocculated in an ethanol solution for 5 times and filtered to obtain a gel sample;

[0187] The gel sample is dried to obtain a composite modified high molecular polymer.

[0188] The rubber mixture is a mixture of styrene-butadiene rubber and EPDM rubber;

[0189] Among them, the mixing mass ratio of styrene butadiene rubber and EPDM rubber is 1:3.

[0190] The solvent is an organic solvent;

[0191] The organic solvent is chlorobenzene;

[0192] The mass fraction of the rubber solution is 12%.

[0193] The mixing mass ratio of formic acid, hydrogen peroxide and rubber solution is 2:1:100;

[0194] The inert atmosphere is a nitrogen atmosphere;

[0195] The mixing mass ratio of rubber solution and modified bentonite is 100:2.5.

[0196] The preparation method of modified bentonite is:

[0197] First, vinyl acetate is added to methanol, and the mixture is stirred and mixed to obtain a vinyl acetate solution;

[0198] Bentonite and stearic acid were added to the vinyl acetate solution in sequence, and then the initiator was added, the temperature was adjusted to 80°C, the mixture was kept warm and stirred for 4 hours, and then cooled to room temperature, filtered, washed, and dried at 60°C for 1 hour to obtain modified bentonite.

[0199] The mass ratio of vinyl acetate to methanol is 1:5;

[0200] The mixed mass ratio of the bentonite, stearic acid and vinyl acetate solution is 4:1.2:14.

[0201] The initiator is dibenzoyl peroxide;

[0202] The mass ratio of dibenzoyl peroxide to vinyl acetate is 1:6.

[0203] S2 Warm-up:

[0204] Preheat the base oil to 180°C and keep warm for 20 minutes;

[0205] S3 step-by-step insulation mixing:

[0206] Add the composite modified high molecular polymer, ethylene triethoxysilane and sodium polyacrylate to the preheated base oil in sequence, and stir for 2 hours under heat preservation;

[0207] S4 step-by-step cooling and mixing:

[0208] The base oil temperature was lowered to 150°C, a thickener was added to the base oil, and the mixture was stirred and mixed for 40 minutes. The temperature was then lowered to 100°C, a flame retardant was added to the base oil, and the mixture was stirred for 2 hours. The mixture was vacuum degassed to obtain a finished product.

[0209] Comparative Example 1:

[0210] Based on the technical solution of Example 2, the difference from the technical solution of Example 1 is that no composite modified high molecular polymer is added.

[0211] Comparative Example 2:

[0212] Based on the technical solution of Example 2, the difference from the technical solution of Example 1 is that no modified bentonite is added during the preparation of the composite modified high molecular polymer.

[0213] test:

[0214] The performance of the sample in Example 2 was tested, as shown in Table 1:

[0215] Table 1

[0216]

[0217]

[0218]

[0219] It can be seen from Table 1 that the cold-applied flame-retardant filling paste for optical cables prepared by the present invention has excellent performance.

[0220] Flash point test was performed on the samples of the embodiment and the comparative example, referring to: YD / T839.1-3.4.3:

[0221] Table 2

[0222] Flash point℃ Example 1 >200 Example 2 >200 Example 3 >200 Example 4 >200 Example 5 >200 Comparative Example 1 >175 Comparative Example 2 >190

[0223] It can be seen from Table 2 that the cold-applied flame-retardant filling paste for optical cables prepared by the present invention has a higher flash point and better flame retardancy.

[0224] The above description is only a preferred embodiment of the present invention, but the present invention is not limited to the scope of implementation shown. Any changes made in accordance with the concept of the present invention, or modifications to equivalent embodiments with equivalent changes, which still do not exceed the spirit covered by the specification, should be within the protection scope of the present invention.

Claims

1. A cold-applied flame-retardant filling paste for optical cables, characterized in that: The invention comprises the following ingredients by weight: 55-80 parts of base oil, 23-25 ​​parts of composite modified high molecular polymer, 10-12 parts of thickener, 1-3 parts of flame retardant, 2-4 parts of ethylene triethoxysilane and 1-1.8 parts of sodium polyacrylate.

2. A cold-applied flame-retardant filling paste for optical cables as claimed in claim 1, characterized in that: The method for preparing the composite modified high molecular polymer comprises: First, the rubber mixture is added to the solvent and stirred to obtain a rubber solution; Adjust the temperature of the rubber solution to 45°C, keep it warm for 20 minutes, and set aside; Formic acid and hydrogen peroxide were added to the rubber solution in sequence, and stirred at 500 r / min for 2 hours under the protection of an inert atmosphere, and then the modified bentonite was added, and the stirring reaction was continued for 4 hours, and then cooled to room temperature to obtain a reaction mixture; The reaction mixture was flocculated in an ethanol solution for 5 times and filtered to obtain a gel sample; The gel sample is dried to obtain a composite modified high molecular polymer.

3. A cold-applied flame-retardant filling paste for optical cables as claimed in claim 2, characterized in that: The rubber mixture is a mixture of styrene-butadiene rubber and EPDM rubber; Among them, the mixing mass ratio of styrene butadiene rubber and EPDM rubber is 1:

3.

4. A cold-applied flame-retardant filling paste for optical cables as claimed in claim 3, characterized in that: The solvent is an organic solvent; The organic solvent is chlorobenzene; The mass fraction of the rubber solution is 10-12%.

5. The cold-applied flame-retardant filling paste for optical cable according to claim 1, characterized in that: The mixing mass ratio of the formic acid, hydrogen peroxide and rubber solution is 2:1:100; The inert atmosphere is a nitrogen atmosphere; The mixing mass ratio of rubber solution and modified bentonite is 100:2-2.

5.

6. A cold-applied flame-retardant filling paste for optical cables as claimed in claim 5, characterized in that: The modified bentonite preparation method is: First, vinyl acetate is added to methanol, and the mixture is stirred and mixed to obtain a vinyl acetate solution; Bentonite and stearic acid were added to the vinyl acetate solution in sequence, and then the initiator was added, the temperature was adjusted to 80°C, the mixture was kept warm and stirred for 4 hours, and then cooled to room temperature, filtered, washed, and dried at 60°C for 1 hour to obtain modified bentonite.

7. A cold-applied flame-retardant filling paste for optical cables as claimed in claim 6, characterized in that: The vinyl acetate and methanol mixing mass ratio is 1:5; The mixed mass ratio of the bentonite, stearic acid and vinyl acetate solution is 3-4:1-1.2:10-14.

8. A cold-applied flame-retardant filling paste for optical cables as claimed in claim 6, characterized in that: The initiator is dibenzoyl peroxide; The mass ratio of dibenzoyl peroxide to vinyl acetate is 1:5-6.

9. A cold-applied flame-retardant filling paste for optical cables as claimed in claim 7, characterized in that: The base oil is fluoroether oil; The thickener is octamethylcyclotetrasiloxane polymer; The flame retardant is magnesium hydroxide.

10. The method for preparing a cold-applied flame-retardant filling paste for optical cables according to claim 1, characterized in that: The following steps are involved: S1 Preparation: Weigh the following according to weight: base oil, composite modified high molecular polymer, thickener, flame retardant, ethylene triethoxysilane, sodium polyacrylate; S2 Warm-up: Preheat the base oil to 180°C and keep warm for 20 minutes; S3 step-by-step insulation mixing: Add the composite modified high molecular polymer, ethylene triethoxysilane and sodium polyacrylate to the preheated base oil in sequence, and stir for 2 hours under heat preservation; S4 step-by-step cooling and mixing: The base oil temperature was lowered to 150°C, a thickener was added to the base oil, and the mixture was stirred and mixed for 40 minutes. The temperature was then lowered to 100°C, a flame retardant was added to the base oil, and the mixture was stirred for 2 hours. The mixture was vacuum degassed to obtain a finished product.